Issues and Concerns of the Elderly in Present Scenario: Understanding and Addressing Social Exclusion among Older People (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The growth of individualism and desire for independence, urbanization and large scale migration for economic reasons of the younger generation all these factors affect the status of the elderly. Factors associated with social exclusion of old people are multiple and are connected with economic and social circumstances which prevent the old people to participate fully in the society. They are excluded from the wider community as well. As a result old people have no voice or recognition in the society in which they live. This article aims to highlight theoretical and operational framework of understanding the social exclusion and its impact among older people in four dimensions. Firstly, the reasons for social exclusion are analyzed. Secondly, the impact of social exclusion and the problems encountered by the elderly are studied. Thirdly, what factors may prevent people from social exclusion at old age is discussed. Social inclusion is important for old people as it would improve the quality of life and independence. So lastly, approaches that can be followed for social inclusion of the elderly in the society are also focused in this paper.